Demonstration of Molecular Tunneling Junctions Based on Vertically Stacked Graphene Heterostructures - Seock-Hyeon Hong; Dong-Hyoup Seo; Hyunwook Song (Crystals, 2022)
We demonstrate the fabrication and complete characterization of vertical molecular tunneling junctions based on graphene heterostructures, which incorporate a control series of arylalkane molecules acting as charge transport barriers. Raman spectroscopy and atomic force microscopy were employed to identify the formation of the molecular monolayer via an electrophilic diazonium reaction on a pre-patterned bottom graphene electrode. The top graphene electrode was transferred to the deposited molecular layer to form a stable electrical connection without filamentary damage. Then, we showed proof of intrinsic charge carrier transport through the arylalkane molecule in the vertical tunneling junctions by carrying out multiprobe approaches combining complementary transport characterization methods, which included length- and temperature-dependent charge transport measurements and transition voltage spectroscopy. Interpretation of all the electrical characterizations was conducted on the basis of intact statistical analysis using a total of 294 fabricated devices. Our results and analysis can provide an objective criterion to validate molecular electronic devices fabricated with graphene electrodes and establish statistically representative junction properties. Since many of the experimental test beds used to examine molecular junctions have generated large variation in the measured data, such a statistical approach is advantageous to identify the meaningful parameters with the data population and describe how the results can be used to characterize the graphene-based molecular junctions.